A Study of the Impact of Degree of Religiousness upon on Individual's Corporate Social Responsiveness Orientation - Kor, Easter Sun Sun (2006)
Recent corporate scandals have once again captured the public attention on Corporate Social Responsibility (CSR). In addition, the issue of corporate social responsibility has receiving increase importance in Malaysia. Since managers make crucial decisions for their organization, their attitudes toward the corporate social responsibility are said to have great impact on the organization. In addition, personal religiousness is argued to have great influence on a person’s corporate social responsiveness orientation. Therefore, this study aims to examine the impact of degree of religiousness upon an individual’s corporate social responsiveness orientation from the Malaysia perspective. This study examined a total of 211 MBA students and working professionals. The study results show that, no significant differences exist with respect to the degree of religiousness upon a Malaysian’s corporate social responsiveness orientation. However, when the study was further examined on each of the religion, the results show that Muslims and Christians tend to have different orientation toward ethical component of corporate social responsibility with respect to their level of religiousness. On the other hand, Buddhists show no difference in their attitudes toward the corporate social responsiveness orientation. Lastly, Hindus are likely to have different attitudes toward the legal component of corporate social responsibility with respect to their level of religiousness.